2023
DOI: 10.1001/jamasurg.2023.2009
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intraoperative Opioid Administration With Postoperative Pain and Opioid Use

Abstract: ImportanceOpioids administered to treat postsurgical pain are a major contributor to the opioid crisis, leading to chronic use in a considerable proportion of patients. Initiatives promoting opioid-free or opioid-sparing modalities of perioperative pain management have led to reduced opioid administration in the operating room, but this reduction could have unforeseen detrimental effects in terms of postoperative pain outcomes, as the relationship between intraoperative opioid usage and later opioid requiremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Previous studies explored the association between opioid use and delirium in individuals with various surgeries and diseases, including hip fractures, neurological injury, pain, infection, fever, and hypotension 4 , 10 , 11 , 30 ; however, investigations focusing on delirium in patients with advanced cancer are limited. A few studies suggested an association between opioid use and the occurrence of delirium in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies explored the association between opioid use and delirium in individuals with various surgeries and diseases, including hip fractures, neurological injury, pain, infection, fever, and hypotension 4 , 10 , 11 , 30 ; however, investigations focusing on delirium in patients with advanced cancer are limited. A few studies suggested an association between opioid use and the occurrence of delirium in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of delirium in these patients is typically multifactorial, and our prior research identified several risk factors for delirium in patients with cancer, including old age, absence of chemotherapy during hospitalization, hearing impairment, underweight status, current opioid use, and history of delirium and other psychiatric disorders 9 . Opioid prescriptions, in particular, have been identified in various studies as potential triggers of delirium, observed across different surgical and disease groups, including those with neurological injury, pain, infection, fever, and hypotension 4 , 10 , 11 . However, previous studies exploring the association between opioid use and delirium in patients with advanced cancer showed controversy and limited cohort size 12 15 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it is unclear based on current available evidence that opioids administered intraoperatively are associated with surgical outcomes or increased risk for aberrant opioid use postoperatively . Recent studies suggested the importance of understanding qualitative and quantitative aspects of intraoperative opioid administrations for postoperative pain and opioid consumption . Characterizing heterogeneity across clinicians and practices may provide valuable insight to elucidate patterns, improve guidelines, and influence policy change to promote better stewardship of opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Available evidence indicates that intraoperative opioid administration is associated with total dosage of opioid consumption and pain level in the PACU after surgery. 2 We are concerned that this unknown factor would have biased the main findings of this study.…”
mentioning
confidence: 96%